Sex slaves and discourse masters : the construction of trafficking - Doezema, Jo (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2010)
Why is the international community so concerned with the fate of prostitutes? And why does the story of trafficking sound so familiar? In this pioneering work, Jo Doezema argues that the current concern with trafficking in women is a modern manifestation of the myth of white slavery. Combining historical analysis with contemporary investigation, Sex Slaves and Discourse Masters examines in detail sex worker reactions to the myth of trafficking, questions the current feminist preoccupation with the 'suffering female body' and argues that feminism needs to move towards the creation of new myths.